[tex]a)\\\\2^{x-4}*8^{3-2x}=4^{3x-3}\\2^{x-4}*(2^3)^{3-2x}=(2^2)^{3x-3}\\2^{x-4}*2^{9-6x}=2^{6x-6}\\2^{x-4+9-6x}=2^{6x-6}\\2^{5-5x}=2^{6x-6}\\\\5-5x=6x-6\\5+6=6x+5\\11=11x /:11\\\underline{x=1}[/tex]
[tex]b)\\\\3^{x+2}-3^x=72\\3^x*3^2-3^x=9*8\\3^x(3^2-1)=9*8 /:(3^2-1)\\3^x=\frac{9*8}{9-1}\\3^x=\frac{9*8}{8}\\3^x=9\\\underline{x=2}[/tex]
[tex]c)\\0.5*4^{2x+4} \geq \frac{1}{256}\\\frac12*(2^2)^{2x+4} \geq \frac{1}{2^8}\\2^{-1}*2^{4x+8} \geq 2^{-8}\\2^{-1+4x+8} \geq 2^{-8}\\4x+7 \geq -8 /-7\\4x \geq -15 /:4\\x \geq -\frac{15}4\\\underline{x\geq -3.75}[/tex]